The Educational Community and the School: A Case Study, by Means of the Combination of Different Techniques, of a Public Secondary School in Argentina - Mirta Giacobbe; Nora Moscoloni; Nora Bolis; Javiera Díaz (Universidad Autónoma de Baja California, 2007)
Research projects in which qualitative and quantitative techniques are combined entail the difficulty of an integral interpretation of the results, due to the particular characteristics of these two approaches. In this article the methodology applied in a case study carried out in an educational institution is described. The study was especially directed towards discovering the particular elements of teacher training which can hinder a constructive teaching practice, ascertaining the role that each of the educational actors performs in the construction of their school, and identifying the characteristics of the educational community that shape the performance of the institution. The study involved the collection, processing and analysis of materials relating to students, teachers, parents and administrators. Each group is addressed methodologically in a different way. Low levels of school performance and difficulties in the integration of the educational community were found. Some proposals for rectifying them are presented here.